Traditional Marriage Customs in Maharjan Community of Lalitpur District: An Ethnographic Exploration - K.C., Ganga (Journal of Population and Development, 2020)
The paper investigates how and why the traditional forms of marriage systems are sustained. This paper describes the marriage practices among Maharjan, and explains how it is anthropologically interesting. The main purpose of this research paper is to examine traditional marriage practices of the Maharjan people as well as the procedures from beginning to end of the marriage. Nepal is a multiethnic and multicultural country along with ecological variation and hidden ethno history. Most of them have their specific language, religion, cultural practices, food habits, festivals, rites and rituals. Among the 59 indigenous ethnic groups of Nepal, the Newars are one of them. Among the different groups of Newar, Maharjan is one sub-group. The present study is ardent to the Maharjan people of Ghachhe Tole of Patan in general and their practice of traditional marriage in particular. This study has been steered by retaining both exploratory cum descriptive research design using the qualitative data. The data of the present study is based on primary as well as secondary sources. In this exploration more detailed account of the traditional marriage practice and processes amongst the Maharjan people is presented in an intricate manner. The entire procedures of the Maharjan marriage, and their innumerable rites and rituals are explained clearly.